Scheduling Maintenance and Determining Crew Size for Stochastically Failing Equipment - Vergin, R. C. (Management Science, 1966)
Past treatment of the single machine maintenance problem has shown that preventive maintenance may be desirable for equipment for which failures are caused at least partially by wear-out factors. In all previous treatment, however, the size of the maintenance-repair crew has been held constant and the optimal maintenance period has then been determined. This paper develops a simultaneous solution for the maintenance-repair crew size and the optimal maintenance period. The optimal maintenance period is seen to shift as the size of the maintenance-repair crew varies. For the multi-machine maintenance problem, the sharing of the maintenance-repair crew creates a queuing system. Because of its complexity, an analytical solution of this multi-machine maintenance queuing system is not feasible. A simulation model was used to develop a set of general rules for scheduling maintenance for the multi-machine case.